Dampak Kebijakan Paten Terhadap Kualitas Pelayanan Publik (Studi Implementasi Paten Di Kabupaten Lima Puluh Kota) - Yossarika; Afrizal; Mahdi (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2024)
Rural development is an effort to improve the quality of life and welfare of the rural communities. Public services provided by local governments are important for regional development. Improvement of public services in the regions can be carried out by the District Government through the District Integrated Administration Services (PATEN) in accordance with the Minister of Home Affairs Regulation Number 4 of 2010. One of licensing that is held through PATEN in the District of Lima Puluh Kota is the Micro and Small Business License. This research combines qualitative and quantitative methods. The research was conducted in Kapur IX and Luak Districts. Data was collected through structured interviews, secondary data, and questionnaries. Data analysis was carried out through the case study technique of Robert K. Yin and Importance Performance Analysis. The results showed that the implementation of PATEN had a good impact on public services and the satisfaction of service seekers reached 96,25%.